Sequence of Sockeye Salmon Type 1 and 2 Growth Hormone Genes and the Relationship of Rainbow Trout with Atlantic and Pacific Salmon - Devlin, Robert H. (Canadian Journal of Fisheries and Aquatic Sciences, 1993)
Two types of growth hormone genes have been isolated from sockeye salmon (Oncorhynchus nerka) and their complete nucleotide sequence determined. The genes encode proteins of 210 amino acids and show considerable similarity to growth hormones characterized in other salmonids and fishes. The two genes presumably arose from a gene duplication event that generated the tetraploid condition in salmonids and are highly conserved in their coding regions. The sequences have diverged approximately 18% in noncoding regions since the gene duplication event and show numerous deletions and/or insertions. Isolation of these two genes from a Pacific salmon allows comparison of their sequences to growth hormone genes characterized from rainbow trout and from Atlantic salmon. The results indicate that rainbow trout is more similar to Pacific than to Atlantic salmon and suggest that Atlantic salmon diverged from Pacific salmonids at a time when sockeye and rainbow trout were part of a common breeding population. These results support the recent reclassification of rainbow trout from the genus Salmo to Oncorhynchus.